2009
DOI: 10.1530/rep-09-0206
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of activin/TGFB-signaling modulators within the normal and dysfunctional adult human testis reveals evidence of altered signaling capacity in a subset of seminomas

Abstract: Activin is a pleiotropic growth factor belonging to the transforming growth factor-b (TGFB) superfamily of signaling molecules. Regulated activin signaling is known to influence several steps in rodent male gamete differentiation. TGFB ligand isoforms, TGFB1-B3, also influence germ cell survival in the rodent testis at the onset of spermatogenesis and around the time of puberty. Given the importance of regulated activin and TGFB signaling in testis development and function, we sought to investigate the cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 63 publications
(78 reference statements)
4
19
2
Order By: Relevance
“…TGFBR3 and its co-receptors and ligands are expressed in most endocrine tissues, including the testis. TGFBR3 has been identified in human Sertoli cells and Leydig cells, both in the normal testis and in tubules with CIS 36. In this study, we found that TGFBR3 was expressed in both Leydig and peritubular cells in fetal as well as adult testis, but was absent from Sertoli cells.…”
Section: Discussionsupporting
confidence: 53%
“…TGFBR3 and its co-receptors and ligands are expressed in most endocrine tissues, including the testis. TGFBR3 has been identified in human Sertoli cells and Leydig cells, both in the normal testis and in tubules with CIS 36. In this study, we found that TGFBR3 was expressed in both Leydig and peritubular cells in fetal as well as adult testis, but was absent from Sertoli cells.…”
Section: Discussionsupporting
confidence: 53%
“…Whether the outcome reported in this study reflects direct or indirect effects on the seminoma cells remains to be determined. The absence of an opposing response in the testis tissues following culture with follistatin suggests that these tumours already contain several mechanisms by which activin signalling is suppressed, as shown previously (Dias et al , 2009) and which can be overcome only by the presence of a highly potent exogenous signalling factor. The investigation of treatment effects in this culture system has clearly demonstrated a specific response, which indicates that the hanging drop culture approach is appropriate for delineation of the specific effects of growth factors, inhibitors and other experimental treatments which will be required to understand the basis of normal testis function and to devise new strategies to ameliorate the burden of testicular pathologies.…”
Section: Discussionsupporting
confidence: 55%
“…Our previous studies have linked activin bioactivity to changes in germ cell differentiation and KIT levels (Mithraprabhu et al , 2010), and we have identified activin receptor expression in human spermatogonia, CIS and seminoma cells (Dias et al , 2008, 2009; Young et al , 2011). We therefore explored the effects of 48 h treatment with activin A and its antagonist, follistatin, on seminoma samples in hanging drop cultures.…”
Section: Resultsmentioning
confidence: 96%
“…These data collectively suggest that Inhba dosage does not have a general effect on transcript levels of the main signaling components in the activin pathway, but instead causes transcriptional changes at specific developmental time points. Using this and other models to understand how the complex milieu of TGFB superfamily signaling components act in the fetal testis is an important challenge that is of relevance to understanding the etiology of testicular cancer in humans [46], where activin and TGFB superfamily receptor subunits, ligands, and inhibitors have been implicated [47,48].…”
Section: Discussionmentioning
confidence: 99%